Guidelines of local wisdom activities organization on improve children’s happiness: Documentary research - Noklang, Sumate; Soopunyo, Weerachat (Saengtham College Journal, 2025)
The purpose of this qualitative was to analyze knowledge related to the concept of improve children’s happiness and, to integrate and synthesize the theoretical framework of guidelines for organizing local wisdom activities to improve children’s happiness. Using of research methodology in documentary analysis by classification of knowledge from 50 copies of documents and research related to the improve children’s happiness. Research were found that: - 1) Knowledge related to improve children’s happiness has 4 factor are children's happiness development, andragogy for improve children’s happiness, leisure activities for improve children’s happiness, and local wisdom learning for improve children’s happiness; -2) the theoretical framework of guidelines for organizing local wisdom activities to improve children’s happiness has 6 factor is Local wisdom learning activities for self-understanding, Local wisdom learning activities for self-development, Local wisdom learning for create success guidelines, Local wisdom learning activities for positive solutions and Local wisdom learning activities for positive self-motivation.